2021
DOI: 10.1007/s10658-020-02181-9
|View full text |Cite
|
Sign up to set email alerts
|

Fulvia fulva [syn. Cladosporium fulvum, Passalora fulva] races in Argentina are evolving through genetic changes and carry polymorphic avr and ecp gene sequences

Abstract: The aim of this work was to study further the population of Fulvia fulva [syn. Cladosporium fulvum, Passalora fulva] in Argentina particularly in terms of diversity at the genetic level by means of ISSR. Also, we studied polymorphisms within avr and ecp sequences, what incidentally might lead to the development of new races. Argentinian tomato cultivars only are affected by two races of F. fulva and the data we provide here indicates that the populations of these two races are under an evolutionary process. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
7
1
1
Order By: Relevance
“…In our study, similar to the previous study, no mutation was detected in the Avr4 gene, and the c.2T>C mutation was detected in the Avr2 gene of all isolates except the Z2/3 isolate. As a result of sequence comparisons, it was determined that the mutations reported in the Avr2 by Novak et al (2021) and the Avr2, Avr4 and Avr4E genes by Lucentini et al (2021) were not found in the isolates sequenced in this study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our study, similar to the previous study, no mutation was detected in the Avr4 gene, and the c.2T>C mutation was detected in the Avr2 gene of all isolates except the Z2/3 isolate. As a result of sequence comparisons, it was determined that the mutations reported in the Avr2 by Novak et al (2021) and the Avr2, Avr4 and Avr4E genes by Lucentini et al (2021) were not found in the isolates sequenced in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Mutations in the Avr2 gene were encoded according to Stergiopoulos, De Kock, et al (2007). Mutations in the Avr4E and Avr9 genes were encoded after the sequences were aligned and cut according to the mutations reported by Lucentini et al (2021). The mating types of the 18 isolates used in this study were determined in a previous study (Gül et al, 2022).…”
Section: Determination Of Polymorphism In Avr Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2012, a number of F. fulva races have been collected from around the world, including Argentina, China, Croatia, Cuba, Korea, Turkey, and the United States, that have overcome resistance provided by one or more of the Cf ‐2 , Cf ‐4 , Cf ‐4 E , Cf ‐5 , or Cf ‐9 immune receptor genes in commercial tomato varieties (Altin, 2016 ; Bernal‐Cabrera et al, 2021 ; Iida et al, 2015 ; Kubota et al, 2015 ; Lee et al, 2013 ; Li et al, 2015 ; Lucentini et al, 2021 ; Medina et al, 2015 ; Mesarich et al, 2014 ; Novak et al, 2021 ; Rollan et al, 2013 ; Sudermann et al, 2022 ; Yoshida et al, 2021 ). Analysis of the allelic variation present in the matching Avr genes has revealed many new mutations, in addition to mutations that had previously been characterized (Stergiopoulos, De Kock, et al, 2007 ), that enable these effectors to escape recognition by their cognate immune receptors (Table 5 ).…”
Section: Induction and Circumvention Of Defence Responses In Tomato B...mentioning
confidence: 99%
“…Una vez obtenidas las colonias, éstas fueron repicadas por siembra de punta de hifa con el propósito de obtener cultivos puros y proceder a su identificación. La identificación fue realizada a partir de las características culturales de los aislamientos obtenidos, de acuerdo con Deschamps y Wright (1975) y mediante la amplificación por la reacción en cadena de la polimerasa (PCR) de la región ITS, utilizando los primers ITS4 e ITS5, siguiendo la metodología descripta por Lucentini et al (2021) y posterior secuenciación en Macrogen (Seúl, Corea). Las secuencias fueron depositadas en el National Center for Biotechnology Information (NCBI) GenBank.…”
Section: Aislamiento E Identificación Fúngicaunclassified